Production and Physicochemical Characterization of Activated Carbon from the Mesocarp of the Coconut (Cocos nucifera L.) Variety Alto del Pacifico - Gabriela Ramos Clamont Montfort; José A. Azamar-Barrios; Patricia Quintana-Owen; Víctor Rejón-Moo; William S. González-Gómez; Tomás J. Madera-Santana (Chemistry)
The mesocarp, a by-product of coconut production, consists of a fibrous outer layer and a medullary tissue. These fibers can be utilized as an alternative source for producing activated carbon (AC). This study presents a method for producing activated carbon from coconut mesocarp fibers (CMFs) using a phosphoric acid (H3PO4) solution as the activating agent. The chemical activation process involves two stages: (1) carbonization of the CMFs, and (2) activation with H3PO4 at elevated temperatures. AC was characterized by its structural, thermal, surface morphological, and elemental properties. The resulting AC developed a lamellar structure with a porous network. Notably, the AC treated with a 60% v/v H3PO4 solution demonstrated a BET adsorption surface area of 1508 m2/g, a total pore volume of 0.871 cm3/g, and an average pore diameter of 2.20 nm. Fourier-transform infrared spectroscopy (FTIR) confirmed the presence of aromatic rings in the AC, while thermogravimetric analysis showed that the AC decomposed at 428 °C, compared to 418 °C for the non-activated carbon. Elemental analysis revealed a 9.04% increase in carbon content in the AC. Producing activated carbon from coconut mesocarp fibers offers a cost-effective method to generate high-surface-area activated carbon from agro-industrial waste.